Permanent magnet flux switching torque performance indicator - Mohd Ab Halim, Mohd Firdaus; Sulaiman, Erwan (TUBITAK, 2021)
Flux switching machine (FSM) offer advantages such as rotor robustness and simple driving circuit compared to competing machine. This paper attempts to process the torque, volume and current information from 35 latest Permanent Magnet (PM) FSM publication into a standardized Torque Performance Indicator (TPI), which are torque density, torque constant, torque constant density and torque-magnet ratio. The distribution median shows that torque density, torque constant, torque constant density and torque-magnet ratio are 23.24kNm/m3, 0.43Nm/A, 0.616Nkm/Am3 and 30.79Nm/kg respectively. Among many design variation, outer rotor configuration produces good values as overall in the TPI. This information can be used to guide the machine designer to compare and compete based on the standardized TPI.